PEMANFAATAN PEMROGRAMAN MULTIUSER UNTUK MANAJEMEN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes): PEMANFAATAN PEMROGRAMAN MULTIUSER UNTUK MANAJEMEN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDes) - Febryantahanuji Febryantahanuji (LPPM STMIK Lombok, 2018)
The Village Fund Budget is a revenue-sharing fund between the District and Village Governments for the welfare of the community. The budget obtained is managed by the village government for development and community welfare. Problems that exist in the preparation of the budget must use a ledger and then make use of Microsoft Excel where it will increase the length of work time because you have to understand excel logic. The absence of databases and security systems that are not yet available is a consideration for the need for a system to conduct management of village expenditure budget management that will make time faster and more accurate in budgeting. Utilization of Visual Basic 6.0 with MySql database and R & D research method developed by Borg and Gall (1983) through the following stages: Research and information collecting, Planning, Develop prelminary form of product, Prelminary field testing, Main product revision, Main field testing . With the use of a system that has integrated the budget management database will be faster and with the existence of a security system which will prevent individuals who are not authorized to manipulate data.